Exploring Career-Related Learning Activities in the Preschool Classroom - Mohamed, Suziyani; Satari, Nor Atiqah; Abu Bakar, Kamariah; Yunus, Faridah (Journal of Technical Education and Training, 2020)
Technical and Vocational Education and Training (TVET) endeavours to developing knowledge and skills of individuals for their future career, and early childhood has been identified as the best period for this purpose because children begin to create career awareness and build up an imagination about the profession that they are interested in. The information regarding the career that children gather at this age will be expanding throughout their life span. Therefore, the purpose of this study is to investigate the practice that is practiced by teachers to urge career exploration among preschoolers in Malaysia. A qualitative study using phenomenology research design was conducted to gather the required information. A total of 24 preschool teachers from a public funded school were interviewed using semi-structured interview questions. The interview session was conducted using a focus group interview technique. Four respondents were interviewed in each group. The data from the interview session were transcribed and a thematic analysis had been conducted. Research findings show that preschool teachers have been practicing some strategies to arouse the curiosity about career among young children. The strategies are introducing career, engaging role-play, referring to role models, watching videos, as well as using career card and mini book. Research has also found that teachers have good perceptions towards career education at an early age. Correspondingly, the findings in this research can be used to plan an appropriate learning approach towards career-related activities among young children. An appropriate learning approach will help to broaden the children’s occupational choices where they will start to think about what they would like to do. As they are growing up, they can narrow down their choices and be more prepared to take related courses that could lead them to the preferred career. Accordingly, the government could consider incorporating career education as a compulsory subject at the early childhood level in the future.